Role of procalcitonin use in the management of sepsis - Gregoriano, Claudia (J Thorac Dis, 2020)
Important aspects of sepsis management include early diagnosis as well as timely and specific treatment in the first few hours of triage. However, diagnosis and differentiation from non-infectious causes often cause uncertainties and potential time delays. Correct use of antibiotics still represents a major challenge, leading to increased risk for opportunistic infections, resistances to multiple antimicrobial agents and toxic side effects, which in turn increase mortality and healthcare costs. Optimized procedures for reliable diagnosis and management of antibiotic therapy has great potential to improve patient care. Herein, biomarkers have been shown to improve infection diagnosis, help in early risk stratification and provide prognostic information which helps optimizing therapeutic decisions (“antibiotic stewardship”). In this context, the use of the blood infection marker procalcitonin (PCT) has gained much attention. There is still no gold standard for the detection of sepsis and use of conventional diagnostic approaches are restricted by some limitations. Therefore, additional tests are necessary to enable early and reliable diagnosis. PCT has good discriminatory properties to differentiate between bacterial and viral inflammations with rapidly available results. Further, PCT adds to risk stratification and prognostication, which may influence appropriate use of health-care resources and therapeutic options. PCT kinetics over time also improves the monitoring of critically ill patients with sepsis and thus influences decisions regarding de-escalation of antibiotics. Most importantly, PCT helps in guiding antibiotic use in patients with respiratory infection and sepsis by limiting initiation and by shortening treatment duration. To date, PCT is the best studied biomarker regarding antibiotic stewardship. Still, further research is needed to understand optimal use of PCT, also in combination with other remerging diagnostic tests for most efficient sepsis care.